ANALYSIS OF POTENTIAL CONFLICT AND PEACEFUL SOLUTIONS AS IMPACT OF STRATEGIC ENVIRONMENTAL DEVELOPMENTS AND ITS IMPLICATIONS ON NATIONAL SECURITY - Arifuddin Uksan (Bajang Institute, 2023)
Developments in the strategic environment can create both opportunities and threats for Indonesia which must be addressed with a national defense system that is able to take advantage of Indonesia's opportunities and advantages to maximize the achievement of Indonesia's strategic interests and counteract all threats to Indonesia's national security arising from the dynamics of developments in the strategic environment. This study aims to analyze the potential for conflict as a result of developments in the strategic environment. This research was conducted with a qualitative descriptive approach. The results of the study indicate that the potential for open conflict escalation in the region is very likely to arise if a misperception or incident occurs at the locus of dispute. The biggest possibility of an open conflict is a battle in maritime theater that occurs in the South China Sea and East China Sea between the US and its allied countries in the Indo-Pacific region and China, or between China and one or more countries that have territorial disputes with China. . Indonesia's geographical position which is at the crossroads of the Pacific and Indian Oceans as well as the continents of Asia and Australia makes Indonesia very vulnerable to spill impacts arising from all conflicts that occur in the Indo-Pacific region.